RELATIONAL DYNAMICS OF STATE LAW AND CUSTOMARY LAW: A STUDY OF THE ULAYAT LAND RIGHTS RECOGNITION - Sukirno Sukirno; Muh. Afif Mahfud (Universitas Syiah Kuala, 2022)
The recognition of ulayat rights is essential in fulfilling indigenous people’s rights. However, the Indonesian government has not fully recognized their rights. This research aims at analyzing the recognition of ulayat right from the Dutch colonial, reformation to the Job Creation Law periods. This is doctrinal legal research focusing on relevant literature. Data are analyzed qualitatively. The research shows that during the Dutch occupation, it is ruled in Agrarisch Wet 1870 followed by Agrarisch Bestluit regulating all lands without provable rights belonging to the state (domein verklaring). Post Indonesia’s independence, Basic Agrarian Law eliminates the Domain Principle and replaces it with State Authoritative Right under Article 33 paragraph (3) of Indonesia’s Constitution. Nowadays, ulayat rights are conditionally recognizable, known as pseudo-recognition. The recognition of indigenous people in the reformation era and post-enactment of the Job Creation Law is too minimal and it strengthens the state’s right over the land.